The Effect Of Solid Fertilizers And Biourine Application On Plants Rice CV Ciherang at Ngujung, Batu, East Java - Mudji Santosa; M. Dawam Maghfoer; Sisca Fajriani (Research Journal of Life Science, 2015)
Ciherang rice is one of the national rice seed production with an average production and potential yield 6 and 8.5 tons/ha respectively. In case of farmers in Batu, the actual production was lower than the average production of Ciherang rice, however there were many natural resources which can support production. Research was aimed to determine the influence of application of synthetic fertilizers and biourine in rice cv Ciherang on farm. It was conducted on Andisol soil, Ngujung, Batu, ca. 24 km from the city of Malang to the northwest at 900 m above sea level (m asl), and average temperature of 22°C. Research was conducted from June to October 2012, by a factorial randomized block design with 2 factors. First factor was application of biourine with 0 (TB) and 1000 l/ha (B). The last factor was application of 6 combinations of fertilizers i.e.: 1) 1st combination of NPK, 150 kg N/ha (urea): 50 kg P2O5/ha ( SP36 ): 70 kg K2O/ha (KCl), 2) 2nd combination of N(50 kg N /ha ( urea ), 25 kg P2O5 /ha (SP36) and 35 kg K2O/ha (KCl), 3) 600 kg/ha of Phonska (NPK; 15 :15 :15), 4) 300 kg/ha of Phonska (NPK; 15 :15 :15), 5) 20 tons/ha of cow manure and, 6 ) 10 tons/ha of cow manure. This experiment was consisted of 12 combinations of treatments and repeated three times. Results showed that averages of plant height, Leaf Area Index (LAI), time of flowering, time of harvesting, the number of tillers plant, number of panicles per culm, number of grains and 1000 grain weight were 88.8 cm, 4.39, ca. 60 days after planting (DAP), 125 DAP, 23.9 plants, 21.6, 152.7 grains/panicle and 26.8 g, respectively. The average highest yield of rice was 1351.7 kg/m2 (by 1st combination of NPK, 150 kgN/ha (urea), 50 kg P2O5/ha (SP36) and 70 kg K2O/ha (KCl) plus 1000 liters of biourine application and the average lowest yield was 796.7 kg/m2 which treated by10 tons/ha cow manure.